Occurrence of Oculo Cardiac Reflex During Strabismus Surgery - Gujjula Shalini; K. Chakrapani; Netra Harsha; Sairani Karanam; Srinivasarao Nambula (Delhi Journal of Ophthalmology)
Purpose: To evaluate the occurrence of the oculocardiac reflex (OCR) and its associated risk factors during strabismus surgery at a tertiary referral center. Methods: Over a 8 months period, all strabismus surgery candidates were enrolled in the study. OCR was defined as heart rate reduction ≥20% after traction on extraocular muscle(s). The rate of OCR was determined and possible associations were explored. Variables included age, gender, type of strabismus, nature of surgery (weakening versus strengthening), and specified extraocular muscle. Results: Eighty four patients with mean age of 17.2 ± 8.7 years were enrolled. OCR occurred in 24 (28.6%) patients, 57 (36.5%) out of 156 operated muscles, and 18 (21.4%) of 23 GA cases. OCR was more common in subjects less than 20 years of age; however, it showed a decreasing trend afterwards. Postoperative nausea and vomiting (PONV) is significantly associated with the occurrence of OCR. OCR was not correlated with gender, type of strabismus, nature of surgery. Conclusion: The great majority of patients undergoing strabismus surgery, especially younger subjects, and those undergoing GA experience OCR during surgery.